Peripheral Artery Embolism as a Complication of Infective Endocarditis in Mitral Insufficiency - Gani Wangunhardjo; Teddy Ontoseno; Soebijanto Poerwodibroto; A. M. Prasodo (Indonesian Pediatric Society Publishing House, 2018)
Injective endocarditis in a 10 years old boy complicated by left brachial artery emboly in a case of rheumatic mitral insufficiency has been reported. The etiologic microorganism was coagulase positive Staphylococci. Though clinical cure was achieved by a 4 weeks long high dose of antibiotic (Ceftriaxone), peripheral artery emboly, had complicated the disease. Since adequate collateral circulation has already occurred, no specific treatment has been given. A further follow-up and injective endocarditis prophylaxis are still needed.